Conocimiento y Prácticas del personal docente con relación al abordaje del proceso de duelo en adolescentes. - Leiva Díaz, Viriam (2012)
The following article presents the partial results on the knowledge and practices of teachers in addressing the grieving teen's Julio Acosta Garcia Higher Institute of San Ramon. This research was performed using a quantitative approach, descriptive. For data collection a questionnaire was used, which allowed to characterize and understand the issues mentioned around the theme of the grieving process in adolescents. The information is grouped according to the systematic study of variables for later analysis. Among the most important findings, it is mentioned that the teachers have little knowledge about the processes of mourning in the period of adolescence, and few personal resources to advice and deal in duels early and timely process management grieving teens. We conclude that it is important that the teachers know what changes that occur during adolescence in the physical, social and psychological, as these can trigger the grieving process that require proper care to avoid the negative implications this may lead also how to intervene in major crisis, as well as some guidelines that will lead to a satisfactory resolution of mourning in this way to properly care for adolescents experiencing this kind of situation.